2014
DOI: 10.1152/ajpregu.00210.2014
|View full text |Cite
|
Sign up to set email alerts
|

Sensitization of sodium appetite: evidence for sustained molecular changes in the lamina terminalis

Abstract: Animals with a history of sodium depletions exhibit increases in salt intake, a phenomenon described as the sensitization of sodium appetite. Using a novel experimental design, the present experiments investigated whether putative molecular markers of neural plasticity and changes in the message for components of the brain renin-angiotensin-aldosterone-system (RAAS) accompany the sensitization of sodium appetite. An initial set of experiments examined whether the glutamatergic N-methyl-d-aspartate receptor ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
11
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 61 publications
(103 reference statements)
2
11
0
Order By: Relevance
“…The elevated levels we found for Agt gene is also consistent with the increased sodium intake of animals with hyperactive brain RAS, inherited, such as in SHR, or genetically engineered, such as in transgenic mice overexpressing neuronal Agt or angiotensin AT 1 receptor genes (18,27). The effect on Agt is also in line with ANG II sensitizing the brain to become more responsive to the pressor effect of ANG II itself and sodium depletion (17,42). In addition, the increased hypothalamic mRNA expression of Anpep induced by WD-PR in HTZ suggests that angiotensins other than ANG II are associated with history of WD-PR.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…The elevated levels we found for Agt gene is also consistent with the increased sodium intake of animals with hyperactive brain RAS, inherited, such as in SHR, or genetically engineered, such as in transgenic mice overexpressing neuronal Agt or angiotensin AT 1 receptor genes (18,27). The effect on Agt is also in line with ANG II sensitizing the brain to become more responsive to the pressor effect of ANG II itself and sodium depletion (17,42). In addition, the increased hypothalamic mRNA expression of Anpep induced by WD-PR in HTZ suggests that angiotensins other than ANG II are associated with history of WD-PR.…”
Section: Discussionsupporting
confidence: 80%
“…Several factors like age, sex, and taste influence sodium intake (8,15,19,41). In addition, ANG II is an established key mediator of sodium appetite sensitization associated with sodium loss (3,17,31,36). Circumstantial evidence also suggests that sensitization to sodium appetite induced by recurrent episodes of WD-PR involves activation of brain ANG II receptors.…”
mentioning
confidence: 99%
“…If this is true, then many of the neural processes that are responsible for sodium appetite (e.g., changes in neurotransmitter release, mRNA expression, or receptor expression) should still be exhibited long after body sodium has been restored. Recent evidence supports this idea as repeated episodes of sodium deficiency produce a long-lasting elevation in mRNA expression across the LT for the angiotensin II receptor type 1, mineralocorticoid receptor, and serum- and glucocorticoid-induced kinase, an intracellular messenger that is activated downstream from the mineralocorticoid receptor [60, 74, 102]. Additionally, sodium depletion appears to produce a long-lasting increase in the expression of Δ fos -B, a molecular marker that has been associated with neuroplasticity, in the SFO [60, 103, 104].…”
Section: Salt Gluttony and The Sensitization Of Sodium Appetitementioning
confidence: 99%
“…In previous studies, sex differences in NaCl intake have been reported after Furosemide ([7] but see [43]). We opted to employ a single episode of Furosemide-induced sodium depletion in order to assess the possibility of estradiol effects on osmotic regulation prior to the establishment of behavioral changes that appear to involve long-term modulation of central pathways [29, 40]. …”
Section: Estradiol Salt and Water Intake And Hypo-osmolalitymentioning
confidence: 99%